Reframing the effectiveness of feedback in improving teaching and learning achievement - Anne Malar Selvaraj; Hazita Azman (Institute of Advanced Engineering and Science, 2020)
Student feedback is established as an imperative learning and teaching technique, but feedback from students is less likely. The potential of feedback to boost learning outcomes refers to scholarly writing and is considered together as one of the most impressive methods for enhancing the success of students. In education, there is, nevertheless a lack of clarification about what feedback means and far less clarification on how one should interpret it. Feedback guides students to learn and supports them in order to achieve the aim of the lesson. The goal of this paper is to discuss teacherwritten reviews and obstacles to student feedback in order to recognise the usefulness of feedback in the education domain. Feedback from students illustrates the comprehensions, boundaries and features that knowledge should be compiled and employed to establish work or learning approach. The assessment study renders the appropriate feedback, and, in this manner, the students learn how to accomplish their learning goals. While feedback is not exclusively evaluated, these are the essential ingredients of making evaluation a mechanism for teachers’ and students’ future learning.